The importance of information and communication technology in reducing the phenomenon of sports fanaticism among university students - Merichiche, khaled (sports creativity, 2025)
This research focuses on the importance of information and communication technology (ICT) in mitigating the phenomenon of sports fanaticism. This phenomenon has recently taken on dangerous dimensions, spreading rapidly among members of the sports community, particularly young people, who constitute the majority of our society. Therefore, our study aims to determine the extent to which ICT, as the most frequently used tools among university students—especially multimedia devices such as mobile phones, social media platforms, forums, and sports websites, which are indispensable for young people today in obtaining their sports information—can reduce and minimize sports fanaticism within the university community. Furthermore, we seek to utilize this technology to raise awareness of the noble values ​​of sports and the importance of sportsmanship in developing the sporting level in our country, transforming sports into a spectacle that contributes to recreation and advancement, rather than fanaticism, aggression, and destruction.